Skeletal muscle loading changes its regenerative capacity - Teixeira, E.; Duarte, J. A. (Sports Medicine, 2016)
Whenever skeletal muscle insults occur, both by functional impositions or other injury forms, skeletal muscle repair (SMR) follows. The SMR succeeds when proper skeletal muscle regeneration and limited fibrosis ensue. Muscle fiber replenishment by fibrosis negatively affects the tissue quality and functionality and, furthermore, represents the worst post-injury phenotypic adaptation. Acute muscle injury treatment commonly follows the RICE method—rest, ice, compression, and elevation. This immediate immobilization seems to be beneficial to preserving the tissue structure and avoiding further destruction; however, if these interventions are delayed, the risk of muscle atrophy and its deleterious-related effects increase, with resultant impaired SMR. Moreover, a growing body of evidence shows positive skeletal muscle loading (SML) effects during SMR since it seems to effectively increase satellite cells (SCs) in their activation, proliferation, self-renewal, and differentiation capacities. Additionally, recent data show that SML may also influence the functions of other participants in SMR, compelling SMR to achieve less fibrotic accretion and accelerated muscle mass recovery. Moreover, given the SML effects on SCs, it is plausible to consider that these can increase the myofibers` basal myogenic potential. Thus, it seems relevant to scrutinize the possible acute and chronic SML therapeutic and prophylactic effects regarding the SMR process.